Promovendo a saúde e prevenindo parasitoses intestinais na área de abrangência do PSF Dr. Salvador Furtado Leite no Município de Ferros/MG - Lindamara Dias (2013)
Parasitic diseases are still considered high prevalence, especially in countries with levels of development and poor living conditions. In this context, there is a lot of individuals who are affected by intestinal parasites. In this work on intervention intestinal parasites, developed by Family Health Team Dr. Salvador Furtado Leite Municipality Irons - MG was conducted a communication process in order to illustrate, demonstrate and consolidate information on intestinal parasites among the population. The communication developed along the sequence of events that occurred during the development of intervention work, conveying and disseminating information related to community participation. The preparation of the plan of action for control of intestinal parasites, children 06-12 years of schools in the catchment area of the Family Health Team Dr. Salvador Furtado Leite, Municipality of Irons - MG performed by three steps: Diagnosis situational, literature review and drafting of the action plan. The results of these interventions were achieved in the long term, however, it was found the enthusiasm of students in relation to what has been learned and their perception of the importance of preventing parasitic diseases by improving the conditions of hygiene and care the home and school environment.